Long-Read Structural and Epigenetic Profiling of a Kidney Tumor-Matched Sample with Nanopore Sequencing and Optical Genome Mapping - Margalit, Sapir; Tulpová, Zuzana; Detinis Zur, Tahir; Michaeli, Yael; Deek, Jasline; Nifker, Gil; Haldar, Rita; Gnatek, Yehudit; Omer, Dorit; Dekel, Benjamin; Feldman, Hagit Baris; Grunwald, Assaf; et al. (bioRxiv, 2024)
Carcinogenesis often involves significant alterations in the cancer genome architecture, marked by large structural and copy number variations (SVs and CNVs) that are difficult to capture with short-read sequencing. Traditionally, cytogenetic techniques are applied to detect such aberrations, but they are limited in resolution and do not cover features smaller than several hundred kilobases. Optical genome mapping and nanopore sequencing are attractive technologies that bridge this resolution gap and offer enhanced performance for cytogenetic applications. These methods profile native, individual DNA molecules, thus capturing epigenetic information. We applied both techniques to characterize a clear cell renal cell carcinoma (ccRCC) tumor's structural and copy number landscape, highlighting the relative strengths of each method in the context of variant size and average read length. Additionally, we assessed their utility for methylome and hydroxymethylome profiling, emphasizing differences in epigenetic analysis applicability.
Keywords: kidney cancer; clear cell renal cell carcinoma; Epigenetics; Optical genome mapping; Structural variations; Long reads; Cytogenetics; Nanopore sequencing